PERANCANGAN SISTEM RESERVASI DAN KASIR RESTORAN BERBASIS WEBSITE STUDI KASUS NYOMAN CAFE - Abdullah, Mikail; I Nyoman Purnama; Ni Putu Noviyanti Kusuma (Jurnal Sistem Informasi (JUSIN), 2025)
The advancement of information technology has driven various business sectors, including the culinary industry, to adopt digital systems to enhance operational efficiency and customer satisfaction. This study aims to design a web-based reservation and cashier system for Nyoman Cafe, a renowned seafood restaurant in Bali. The system addresses challenges in manual reservations and transaction recording, which often lead to errors, delays, and data inaccuracies. Utilizing the Prototipe method, the research involves stages of requirement gathering, interface design using Figma, and Prototipe evaluation to ensure the system aligns with user needs. The resulting system enables customers to make online table reservations with real-time availability access while simplifying transaction management through automated record-keeping features. This system is expected to improve operational efficiency, minimize errors, enhance customer experiences, and strengthen Nyoman Cafe's competitiveness in the culinary industry.